Kenaf as natural resource for lactic acid production - Mohd. Nasir, Nur Aimi; Mustafa Kamalbhrin, Mohd. Adlan; Seeni Mohamed, Nurhafizah; Anuar, Hazleen; Mel, Maizirwan; Othman, Rashidi (2011)
Kenaf biomass indicates promising choices to produce lactic acid via fermentation by Rhizopus oryzae. The pre- treatment process was done on kenaf biomass with dilute sulphuric acid (H2SO4) to hydrolyze the cellulose content in it. The step was then continued with the fermentation process in shake flask which was at 25 oC at 150 rpm, 25 oC at 200 rpm, 37 oC at 150 rpm and 37 oC at 200 rpm. This fermentation process was conducted for 3 days at pH 6. In this fermentation process, 0.471 g/L, 0.428 g/L, 0.444 g/L and 0.38 g/L of lactic acid was produced respectively. Sample at 25oC at 200 rpm produced maximum amount of lactic acid compared to others.